2021
DOI: 10.1186/s13287-020-02095-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of stem cells therapy for Crohn’s fistula: a meta-analysis and systematic review

Abstract: Background Fistulas have puzzled us all the time and stem cell therapy for it is still in its infancy. We conducted a meta-analysis and systematic review to evaluate the efficacy of stem cells and its potential mechanisms in the management of Crohn’s fistula. Methods Electronic databases were searched comprehensively for studies reporting the efficacy and safety of stem cells in patients with any form of Crohn’s fistula. A random-effects model was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 87 publications
(132 reference statements)
0
38
0
1
Order By: Relevance
“…A metaanalysis and systematic review reported that patients receiving MSCs transplantation had a higher rate of fistula healing than patients receiving placebo (61.75 vs. 40.46%, P < 0.05). MSCs transplantation, especially ADSCs, was well-tolerated with a lower incidence of adverse events than placebo (195).…”
Section: Mscs Transplantationmentioning
confidence: 96%
“…A metaanalysis and systematic review reported that patients receiving MSCs transplantation had a higher rate of fistula healing than patients receiving placebo (61.75 vs. 40.46%, P < 0.05). MSCs transplantation, especially ADSCs, was well-tolerated with a lower incidence of adverse events than placebo (195).…”
Section: Mscs Transplantationmentioning
confidence: 96%
“…According to a meta-analysis based on four clinical trials involving different doses of stem cell therapy ranging from 1 × 10 7 to 9 × 10 7 MSCs per mL, the dose of 2 × 10 7 and 3 × 10 7 cells/mL were characterized by a highest rate of fistula healing in Crohn's patients [17]. However, the mentioned study is strongly limited by a low number of included patients (n = 31).…”
Section: Mesenchymal Stem Cells Application In Perianal Crohn's Diseasementioning
confidence: 99%
“…Additionally, beyond the surgeries discussed in this review, it is important to note that other treatment methods, such as stem cell transplantation, have shown some degree of efficacy. A recent meta-analysis of Crohn’s fistula patients treated with stem cell transplantation utilized data from 7 studies of RVF and found a healing rate of 27.2% [ 32 ].…”
Section: Discussionmentioning
confidence: 99%